2014
DOI: 10.1253/circj.cj-13-1029
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Profiles of the Ductus Arteriosus in Brown-Norway Rats With Irregular Elastic Fiber Formation

Abstract: Background: Patent ductus arteriosus (PDA) is one of the most common congenital cardiovascular defects in children. The Brown-Norway (BN) inbred rat presents a higher frequency of PDA. A previous study reported that 2 different quantitative trait loci on chromosomes 8 and 9 were significantly linked to PDA in this strain. Nevertheless, the genetic or molecular mechanisms underlying PDA phenotypes in BN rats have not been fully investigated yet. Methods and Results:It was found that the elastic fibers were abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Several transcriptomic studies have been reported previously in mice and rats; however, these have had different experimental designs or utilized single developmental time points for comparison, thereby limiting their ability to identify genes whose developmental changes are unique to the DA (26). A study in the rat examined changes in gene expression between DA and aorta at day 19 and 21 (3). We reanalyzed the microarray data from this study and compared it with the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Several transcriptomic studies have been reported previously in mice and rats; however, these have had different experimental designs or utilized single developmental time points for comparison, thereby limiting their ability to identify genes whose developmental changes are unique to the DA (26). A study in the rat examined changes in gene expression between DA and aorta at day 19 and 21 (3). We reanalyzed the microarray data from this study and compared it with the present study.…”
Section: Discussionmentioning
confidence: 99%
“…After centrifugation at 12,000 g at 4˚C for 15 minutes, the supernatant was collected. Microarray analysis was performed as previously described [5,6]. Briefly, total mRNA was extracted following the instructions attached to the kit.…”
Section: Microarray Analysismentioning
confidence: 99%
“…Tropoelastin is a chemoattractant for SMCs. Lysl oxidase (LOX) catalyzes elastin cross-linking and it is degraded in the ductal cell when EP 4 receptor is stimulated by the prostaglandins ( 77 ). EP 4 is a Gs protein coupled receptor which increases intracellular cAMP by adenylyl cyclases.…”
Section: Anatomic Closure and Remodelingmentioning
confidence: 99%